2017
DOI: 10.5455/ajvs.276323
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Supplementation of Moringa Oleifera in Diet of Broiler Chicks on Their Behavior, Welfare, Performance and Immune Responses

Abstract: A total of two hundred and four, one day old Ross broiler chicks were randomly allotted into four dietary treatments floor pen groups (17 birds/ pen, 10 birds/m 2 ) with three replicates for each treatment. The dietary treatments were designed to feed the chick's basal diet supplemented with graded levels of Moringa oleifera leaves meal, MOLM [3%, 5%, 8% and 0% (control) MOLM]. Behavioral observation was carried out twice daily (AM,(7)(8)(9)(10)(13)(14)(15) two days a week for 6 consecutive weeks. Body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Moringa has high biomass yield and crude protein (CP, 25%) and a balance of other nutrients, such as neutral detergent fibre (NDF, 21.9%), acid detergent fibre (ADF, 11.4%) and lipid (5.4%), in the leaves (Makkar & Becker, ). In broilers, diets supplemented with 80 g/kg and 110 g/kg Moringa oleifera leaves increased the final body weight and body weight gain (Melesse, Getye, Berihun, & Banerjee, ; Ramadan, ). Additionally, dietary supplementation of 15% and 20% Moringa oleifera leaves improved the morphology of the bursa, thymus and spleen of broilers (Alnidawi, Ali, Abdelgayed, Ahmed, & Farid, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moringa has high biomass yield and crude protein (CP, 25%) and a balance of other nutrients, such as neutral detergent fibre (NDF, 21.9%), acid detergent fibre (ADF, 11.4%) and lipid (5.4%), in the leaves (Makkar & Becker, ). In broilers, diets supplemented with 80 g/kg and 110 g/kg Moringa oleifera leaves increased the final body weight and body weight gain (Melesse, Getye, Berihun, & Banerjee, ; Ramadan, ). Additionally, dietary supplementation of 15% and 20% Moringa oleifera leaves improved the morphology of the bursa, thymus and spleen of broilers (Alnidawi, Ali, Abdelgayed, Ahmed, & Farid, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ramadan [27], stated that body weight gain was significantly higher in all Moringa oleifera leaf meal (MOLM) treated groups (0.3, 0.5 and 0.8%) compared to control birds. Average feed intake as affected by addition of different levels MOLP are presented in (Table 4).…”
Section: Resultsmentioning
confidence: 97%
“…This finding further suggested that dietary supplementation of MLM can reduce the level of stress in laying hens. This could be attributed to the hepatoprotective, antioxidant and antimicrobial properties of MLM (Ramadan, 2017).…”
Section: Resultsmentioning
confidence: 99%